Inconstitucionalidad de la expropiación señalada en el código de procedimiento civil, por su justa valoración, pago e indemnización con la ocupación conforme a la ley previsto en la constitución de la república del Ecuador. - Aguayo Aroca, Ángel Eduardo (2010)
The development of this research study unconstitutional the expropriation referred to in the Code of Civil Procedure, for its fair valuation, payment and compensation to the occupation under the law under the Constitution of the Republic of Ecuador, reasoning that serves to establish in the trial of expropriation is canceled prior fair value until it is resolved in final sentence payment of expropriated land have come to engage the parties. In this study, we analyzed in detail, the conceptualization that includes the expropriation of public interest on social interest, the fair price, prior fair valuation, making it one of the limiting factors of our legal system, which comes to constitute unconstitutional According to what is stated in the Constitution of the Republic of Ecuador. This study of the prior fair valuation becomes enshrined in the Constitution of the Republic of Ecuador, but in the trial of expropriation, which decides the price of the expropriated property identified in the Code of Civil Procedure is unconstitutional, because in him, just prior valuation is canceled there because once the process moves of res judicata.